Student belief about the value of challenge. (8th August 2019) - Rudland, JR; Golding, C; Jaye, C; Tweed, M; Wilkinson, TJ
Summary: Background: The undergraduate curriculum tends to focus on how individuals can cope with stress especially when transitioning from the classroom to the clinical workplace environment. Often this carries the message that stress is bad, yet little attention has been paid to the influence of one's belief regarding the value of stress for learning. Because stress is often perceived as bad, we chose to use the term 'challenge' in exploring the associations amongst belief of the value of challenge, the challenge experienced, the perceived learning, affect and staff support. Methods: At the end of each clinical module within a medical curriculum, medical students rated the perceived learning, degree of challenge, affect, support and the value of challenge for learning. The value and associations amongst these variables were analysed. Results: The challenge for students varied according to the type of module. Students generally considered that challenge promoted rather than hindered learning. The level of challenge experienced may influence the perception of the value of challenge for learning. However, when challenge was regarded as beneficial, this was strongly, positively associated with perceived learning, positive affect and support. Discussion: Students who believe challenge is positive also perceive that such challenges promote learning. Likewise students who regard challenge as negative are less likely to learn from such challenges. The positive relationship between the belief of the value of challenge with affect and support may have positive implications for well‐being. It is contended that curriculum planners should acknowledge the potential positive influence of stressors in clinical education and that challenge can be seen as valuable when there is student support and measures associated with maintaining a positive affect.